Beyond national borders: reframing the global brain drain debate - Tannock, S (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2007)
Economic and education policy in the UK, as in most other nations today, emphasises raising overall skill and education levels as the principal way to improve individual and societal well-being. Such policy, however, is challenged by the widespread phenomenon of “brain drain” – that is, the movement of the highly educated across national borders, as well as across regions, industries and occupations, movements that repeatedly leave some areas of society and the economy desperately short of much needed talent and labour. What matters in addressing brain drain is not simply how much skill and education individuals and societies have, but the kinds of skill and education involved, the social and political ends to which they are put, and the economic and cultural incentives that drive individuals toward some corners of the global labour market and away from others. To resolve the brain drain problem, we need to create societies based not just on elevated levels of knowledge, skill and education, but first and foremost, on firm commitments to protecting the public interest, broadly defined. The following paper extends this argument through a critical reading and reframing of the global brain drain policy and academic research literature.